Headache in an HIV-Positive Patient: Dangerous Interaction. (4th June 2018) - Iardino, Alfredo; Garner, Orlando; Lorusso, Gabriella; Lotta, Franco
Abstract : Ergotism is an ischaemic complication due to vasoconstriction throughout the body due to ingestion of ergotamine. A 34-year-old Hispanic man with HIV infection treated with saquinavir, ritonavir and abacavir/lamivudine presented to the emergency department complaining of left foot pain 1 week prior to admission. The affected extremity was cold with absence of pedal and tibial pulses. Arterial Doppler revealed absent arterial flow from the popliteal artery later confirmed by arteriography. Medication reconciliation revealed a recent prescription for migraine headache containing ergotamine. Drug was discontinued and the patient was started on cilostazol, enoxaparin and nitroglycerin patches on the affected limb. Complete resolution of symptoms and arteriography findings occurred 2 days after therapy began.